Ketidakstabilan Emosi dan Mood Masyarakat Dimasa Pandemi Covid-19 - Dira Anjania Rifani; Dedi Rianto Rahadi (Jurnal Manajemen dan Bisnis, 2021)
The Covid-19 pandemic has a major impact on all aspects of life. One of the effects of the Covid-19 pandemic is human mental health. Human mental health related to emotions and moods is an important factor in carrying out all human activities. The emotional stability and mood of an individual are influenced by heredity, environment and current circumstances. In the midst of the Covid-19 pandemic, everythings have changed drastically from usual, people are forced to be able to face the pressure that occurs from a social, economic and cultural side. Therefore, special attention is needed so that this pandemic can all be passed even though it is more difficult and complicated. The formulation of the problem is how the Emotional Instability and Mood of the Community During the Covid-19 Pandemic. This study uses a causal research design and adopts qualitative research methods with subjects consisting of parents, students, workers, and business people. The results of his research are that the Covid-19 pandemic certainly has a major negative impact on people's mental health, which begins with stress, anxiety and fear in the community and then leads to conflicts within the family, environment, and country.